Environment-Based Bilingual Learning Integration in Education at Darul Hikmah Modern Islamic Boarding School Tulungagung - Lusi Andriani; Suripto; Benny Prasetiya; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
This study aims to analyze the integration of environment-based bilingual learning within the educational system of Pondok Pesantren Modern Darul Hikmah Tulungagung and its implications for students’ language competence and character development. A qualitative descriptive approach was employed, using in-depth interviews, participatory observation, and document analysis. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that bilingual learning is integrated through the synergy between the national curriculum and the KMI curriculum, institutional language policies, and the reinforcement of a language-rich environment as an immersion space. The pesantren environment functions as an authentic practice setting where academic, social, and religious activities support daily language use. This model enhances students’ language fluency, self-confidence, and the internalization of Islamic values. This study highlights that the success of bilingual learning is determined not only by curriculum design but also by a supportive and sustainable learning environment. The novelty of this research lies in proposing an environment-based bilingual integration model within the KMI system that holistically combines pedagogical, cultural, and religious dimensions.